Sharing of gis spatial data intransportation engineering - Mohd. Yunus, M. Z. (Penerbit UTM Press, 2016)
Geographic Information System (GIS) is classified as an information technology to solve various spatial problems in civil engineering. GIS provides spatial information to the system and therefore, complex spatial analysis of problem could be carried out. The objective of this paper is to promote the use of GIS as a tool for civil engineering problem solving. This paper describes the work undertaken to demonstrate the potential use of GIS in civil engineering via a prototype project. The presentation of this article is mainly focused on the applications of GIS in transportation engineering including transportation, highway and traffic. Moreover, this study could also contribute relevant and benefit guidance to the public and private sectors with techniques in determining potential activity using the GIS software. The utilisation of GIS can prepare and contributes towards a profitable cost and effective service. The end product should be an effective information system and a final potential GIS map. With GIS support, it could assist user to make a more effective and efficient decision on any difficulties that will arise. Compared to the conventional methods, the system provides a proper and an effective, update and accessible result of spatial analysis.